Comprehensive assessment of the level of innovative development of the enterprise - Oliferuk, S.L.; Halunka , O.D.; Mіronov, O.O. (Ways to Improve Construction Efficiency, 2021)
This article examines a comprehensive assessment of the level of innovative development of an enterprise. A number of indicators are proposed that allow one to evaluate and determine the necessary innovative directions and formulas for their calculation. The list of characterizing indicators (such as an increase in the coefficient of the level of innovative renewal of the active part of fixed assets, a decrease in the coefficient of the level of the duration of one complete turnover of working capital, an increase in the coefficient of the level of labor productivity (output), an increase in the rate of return on wages, a decrease in the rate of current costs per unit of marketable output, an increase in the rate of product quality, the rate of costs for ensuring a high level of quality, the rate of cost of rejected products, the rate of return on assets, renewal coefficient, duration of one full turnover in days, turnover ratio of working capital, annual output of one worker in monetary terms, labor intensity of a unit of production, indicator of total costs of production resources per unit of manufactured commodity product, coefficient of profitability (profitability) of products, indicator of profitability of own capital investments , payback period of own capital investments) allows to carry out a comprehensive assessment of the level of innovative development of the enterprise and determine the necessary innovative directions. The competitiveness of an enterprise is a complex system of innovative technical and economic means of effective (economical and rational) use of production potential and production resources, provides a high level of quality, self-sufficiency and self-financing, profitability and profitability, as well as an advantage over competitors in technical and technological terms. One of the main factors in the economic provision of the level of competitiveness of the enterprise is the appropriate provision of a high level of product quality.